DAKWAH BERBASIS MEDIA DAN KOMUNIKASI VISUAL - Ari Wibowo (Jurnal Bimbingan Penyuluhan Islam, 2020)
This article describes the concept of digitizing da'wah based on visual communication design. The advancement of information and communication technology disrupts various aspects of life including how to preach the da'i. This is both a challenge and an opportunity for preachers to develop da'wa media that are relevant to today's civilization. One of the concepts offered is a visual communication design. This design concept is very relevant to today's conditions (digital era) and can be a reference for preachers, especially for packaging creative and interesting da'wah content on various social media platforms. This article is enriched with literature studies to clarify the concept of visual communication and its relation to da'wah. The observation technique is used to provide an overview of the portrait of visual communication design which is applied in the preaching of Facebook, YouTube, and the website. As a result, there are four social media that can be used as a media for preaching based on visual communication, namely, Facebook, WhatsApp, Instagram, and YouTube. Furthermore, there are three forms of digital communication based on visual communication that is widely used in social media, namely da'wah posters, da'wah cartoons, and da'wah videos.